Female voice in Nepali Art - Rajbhandari, Jasmine (Journal of Fine Arts Campus, 2023)
The emergence of female voices in Nepali art noticeably began in 1989. The recent practices of female Nepali artists not only represent their personal emotional experiences but also convey strong messages. Their work talks about the various challenges faced by women in the patriarchal society of Nepal, and aims to bring positive changes such as equal space and freedom from social barriers. They not only address gender issues, but also question the right to give birth and abortion. Additionally, they address social disorders such as rape, Chhaupadi practices, untouchable issues during menstruation, and many other political issues in their work. This writing is based on qualitative research design and explores the work of ten Nepali women artists, using the theory of Feminism. Today, Nepali art is rapidly developing due to globalization and education. One of the main reasons for this progress is the rise in consciousness and education of female artists. They have demonstrated unique vision and creativity to lead the entire genre towards a better future. National and international art galleries exhibit their works, and even international museums collect their pieces. Their work is attracting the art market and also is getting critical acclaims.